2010
DOI: 10.1037/a0018403
|View full text |Cite
|
Sign up to set email alerts
|

The desire to expel unselfish members from the group.

Abstract: An initial study investigating tolerance of group members who abuse a public good surprisingly showed that unselfish members (those who gave much toward the provision of the good but then used little of the good) were also targets for expulsion from the group. Two follow-up studies replicated this and ruled out explanations grounded in the target being seen as confused or unpredictable. A fourth study suggested that the target is seen by some as establishing an undesirable behavior standard and by others as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 38 publications
7
87
0
1
Order By: Relevance
“…Our measures of social rejection, however, did hint that atypical cooperators were slightly less likely to be preferred for subsequent hypothetical interactions, when player 5 would then be in the group with this individual. This tendency, although weak, supports previous work showing that excessively helpful, cooperative or moralistic individuals might be viewed negatively rather than positively by others in their social group [9,11,23,24]. …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our measures of social rejection, however, did hint that atypical cooperators were slightly less likely to be preferred for subsequent hypothetical interactions, when player 5 would then be in the group with this individual. This tendency, although weak, supports previous work showing that excessively helpful, cooperative or moralistic individuals might be viewed negatively rather than positively by others in their social group [9,11,23,24]. …”
Section: Discussionsupporting
confidence: 84%
“…It is possible that defectors were punished regardless of their prevalence, because individuals did not make punishment decisions based on the events in the game but instead on a pre-existing perception of defection as a norm violation formed from their experience in the ‘real world’. However, previous studies in the same cultural group (US-based subjects) have shown that individuals' behaviour is sensitive to similar social norm manipulations that occur within the confines of the game setting [9,11]. …”
Section: Discussionmentioning
confidence: 99%
“…Before turning to the implications of our findings we wish to address a limitation of our sanctions instead appear to be related to patience and impulsivity (10,11), normative considerations (7,(12)(13)(14)(15), and genetic correlates of aggression (16).…”
Section: Discussionmentioning
confidence: 99%
“…The strongest evidence suggestive of a common-moral association comes from studies finding that moral judgments of socially undesirable behavior tend to be less harsh when the behavior is perceived to be common (McGraw, 1985;Trafimow, Reeder, & Blising, 2001;Welch et al, 2005), and that people seem to find fault both with singular selfishness and singular generosity in others (Parks & Stone, 2010).…”
Section: Observations Suggestive Of a Common-moral Associationmentioning
confidence: 99%